Improving the quality of life through Balneotourism practices: the Bulgarian experience - Stankova, Maria Zl.; Kirilov, Stefan Y. (Wydawnictwo Uniwersytetu Wrocławskiego, 2017)
Balneotourism is a traditional element of Bulgaria’s tourist destination image. The use of the healing powers of water, climate and mud deposits can be traced back to the old Thracian tribes that inhabited Bulgarian lands thousands of years ago. Bulgaria can successfully develop balneotourism and boost foreign visitors not only with its available natural resources, but also with great affordability of the health services offered. This is an opportunity to overcome the problem of season dependent tourism, as well as to increase revenues in the sector and the economy. At the same time, balneotourism and the establishment of the national health system allow for a real improvement in the quality of life of all the insured but particularly of people with disabilities. In that regard, the present paper analyses the origins, development and the current state of balneotourism in Bulgaria. Special attention is paid to defining the terms “balneology” and “balneotourism”. There are theoretical issues observed as well as significant aspects of the Bulgarian health system related to the utilization of the balneotourism product. Based on conducted research and analysis, recommendations are made aiming at further development of balneotourism and improvement of the quality of life of people with medical conditions and the disabled
Keywords: balneoturystyka; balneologia; wody mineralne; leczenie balneologiczne